Effect of Structural Forms on Wind-Induced Response of Tall Buildings: A Finite Element Approach - Paraskevi Mazarakou; Angeliki Papalou (Eng, 2025)
Tall buildings are vulnerable to wind loads, which can cause significant displacements that can affect their stability, strength, and serviceability. Their structural configuration can significantly influence their behavior to wind loads. There are not enough comparative studies in the literature examining the effects of wind loads on different structural configurations. This study examines the response of tall buildings to wind loads by varying their structural forms. Twelve models of tall buildings of different heights and structural configurations were analyzed using the finite element method. Wind loads were applied to the models as equivalent static forces, according to existing codes. The maximum displacements were calculated for each model, and the results were compared. It was found that a considerable reduction in the response was achieved by including shear walls at specific locations in the building’s layout, thereby identifying the optimal location. However, the effectiveness of the different configurations converges at building heights greater than 120 m. In addition, the maximum displacement on the same floor in buildings with the same structural form may vary depending on the building’s total height. An increase in wind velocity results in an almost linear increase in the maximum displacements of the buildings. The findings of this study can assist designers in optimizing shear wall placement in tall building designs.